KOŠARKA NA PROSTORIMA BIVŠE JUGOSLAVIJE TOKOM 1941. GODINE - Slobodan Simović; Petar Pavlović; Kristina Pantelić; Zrinko Grgić (University of Banja Luka, Faculty of physical education and sport, 2010)
Development of basketball in the territory we are talking about, during the WW II, remained quite un-researched, so the subject and the goal of this paper is to research, analyze, highlight and obtain from oblivion that same period. We hope to stir up the sports historians, and also other readers interested in history of sports for further research. During writing usual historical method was used (finding of primary historical sources, their critics, as also the finding and studying of the secondary historical sources) . A numerous sources made in that time were reviewed and consulted (magazines, newspapers, papers, records, reports, overwrites, etc.) in: archives, libraries, institutes, private archives and museums of sports of for-mer Yugoslavia, as also the sources made afterword. During 1941 basketball took place in Belgrade, Novi Sad, Split, Šibenik, Dubrovnik and Ko-tor. The competitions were played occasionally but most intensively in Belgrade. Serbian Basket -ball Federation was founded in September, also in Belgrade.